Features of the vegetative state and arterial pressure level in children with chronic gastroduodenal pathology - A. S. Hotsulia (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki, 2018)
Introduction. Heterocyclic compounds are the foundation on which the creation of medicines is successfully carried out. One such system is 1,2,4-triazole and 3-methylxanthine. These heterocycles are characterized by wide range of biological properties, along with low toxicity.